Assessing the distribution pattern of otters in four rivers of the Indian Himalayan biodiversity hotspot. Issue 3 (27th January 2020) - Gupta, Nishikant; Tiwari, Varun; Everard, Mark; Savage, Melissa; Hussain, Syed Ainul; Chadwick, Michael A.; Johnson, Jeyaraj Antony; Nawab, Asghar; Belwal, Vinod K.
Abstract: The Eurasian otter ( Lutra lutra ), smooth‐coated otter ( Lutrogale perspicillata ), and Asian small‐clawed otter ( Aonyx cinereus ) have all been reported previously from the Indian state of Uttarakhand. However, little information is available about their current distribution in a mountainous region that is subject to increasing human‐induced stressors (such as hydropower plants, pollution, sand and boulder mining, destructive fishing techniques, poaching). Owing to important roles played by these otters in structuring riverine food webs (particularly taking account of their roles as top carnivores), it is critical that they receive suitable protection in the face of projected temperature rise, change in precipitation patterns, and associated river flows in this Himalayan biodiversity hotspot. This study assesses otter distribution in four rivers of Uttarakhand as a basis for informing future conservation actions. Field surveys were conducted (October 2018–January 2019) in reaches of the Kosi, Ramganga, Khoh, and Song rivers, supported by semi‐structured interviews ( N = 379) conducted with members of local communities to collect qualitative data on views and perceptions of otter species. In addition, community‐based otter awareness camps were organized for local youths ( N = 105), adults ( N = 115), and schoolchildren ( N = 256 covering 10 schools). Habitat suitability maps were created using remote‐sensing data, survey findings, and a geographic information system to provide information about priority reaches of river to be targeted for future conservation efforts. This study provides critical interdisciplinary baseline information to guide decision‐makers towards developing a targeted, otter‐specific conservation programme for this important Himalayan biodiversity hotspot. The otter conservation education programmes conducted during this study resulted in a proposal to set up a community‐based conservation initiative to monitor and report otter sightings from the area, potentially representing a way forward for achieving simultaneous otter conservation and associated ecosystem benefits for local communities.